Proactive Safety Measure Using Road Environment Assessment Program (REAP) - Mohd Razelan, Intan Suhana (International Journal of Integrated Engineering, 2019)
In Malaysia, reactive crash statistics have becoming very crucial in evaluating roadâ€™s safety level and in deciding crash-prone areas known as black spot. The establishments of these statistics normally take years to complete as a result of several well-known setbacks within developing countries. Those obstacles had produced poor crash database having low accessibility, reliability and adequateness of crash data that finally brought major impact to the entire road safety system.Â  In light of that, a proactive safety measure called Road Environment Assessment Program (REAP) has been developed to help evaluating the environment risk factors of a road, calculating the risk index and presented the results through Google Earth platform. REAP was developed based on composite risk index value aggregated from 14 road environment indicators existed in most Malaysia federal roads. Based on the local conditions of the selected roads, specific road environment risk factor were produced where trend and risk level as well as identifications of riskiest road section could be easily identified. REAP is a time-saving and cost-saving tool as it can directly recognize problematic road environment factors while planning on the best and suitable road improvement procedures for problematic sections.